Aerospace sensors - Nebylov, A. V. (Aleksandr Vladimirovich) (Sensor technology series., 2013)
The present series is concerned with sensors per se, and because the subject matter is so wide-ranging in both scope and maturity, this must be reflected within the individual volumes. So, whereas care has been taken to include a considerable amount of practical material, the proportion of such leavening is inevitably variable. The present volume will be found to include material on the basic processes that are addressed by the sensors used in most aspects of aerospace technology, plus considerable detail on the relevant sensors themselves and their applications. In the context of aerospace engineering, however, there are many items of complex equipment--mostly radio and navigationally oriented--that can be considered as sensors in their own right. This situation has been addressed in a companion volume that is in production at the time of writing, and will act as an adjunct to the present work.